2021
DOI: 10.1159/000521499
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Drug Conjugates for Breast Cancer

Abstract: Background Despite the advances that have been made to improve conventional chemotherapies, their use is limited by a narrow therapeutic window based on off-target toxicities. Antibody-drug-conjugates (ADCs) are composed of an antibody and a toxic payload covalently coupled by a chemical linker. They constitute an elegant means to tackle the limitations of conventional chemotherapeutics by selectively delivering a highly toxic payload directly to target cells and thereby increasing efficacy of the delivered cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Ideally, the target antigen should be tumor specific and preferentially expressed in tumor tissues but lowly expressed in non-tumorigenic tissues. Moreover, the target antigen must be easily accessible to antibody binding to facilitate effective internalization and delivery of the active cytotoxic drug into the tumor cell [ 115 , 116 ]. Currently, two antigens are approved for targeting breast cancer with ADCs, HER2 and TROP2.…”
Section: Antibody-drug Conjugates For Her2-positive Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the target antigen should be tumor specific and preferentially expressed in tumor tissues but lowly expressed in non-tumorigenic tissues. Moreover, the target antigen must be easily accessible to antibody binding to facilitate effective internalization and delivery of the active cytotoxic drug into the tumor cell [ 115 , 116 ]. Currently, two antigens are approved for targeting breast cancer with ADCs, HER2 and TROP2.…”
Section: Antibody-drug Conjugates For Her2-positive Breast Cancermentioning
confidence: 99%
“…The compatibility and specificity of the antibody is critical for the activity of an ADC. The mechanism of action of ADCs relies on the internalization of antibody-bound antigens for the delivery of cytotoxic agents [ 115 , 116 ]. Hence, the antibody must have a high affinity to the target antigen to achieve maximum effect while reducing cross-reactivity that may reduce efficacy of the cytotoxic component of the ADC [ 122 ].…”
Section: Antibody-drug Conjugates For Her2-positive Breast Cancermentioning
confidence: 99%
“…In a study presented by Marme [ 125 ], it was shown that there are currently nine approved ADCs, including three for breast cancer. With over 100 candidates in various stages of clinical development, the rate of development appears to be quickening.…”
Section: Resultsmentioning
confidence: 99%
“…However, more than 60 ADCs are at different stages of development for use in breast cancer patients, including several trials for TNBC, with molecular targets such as TROP-2, LIV-1, HER2, HER3 and ROR2, amongst others. The selected agents included in this review are trastuzumab deruxtecan (T-DXd) (NCT04556773), ladiratuzumab vedotin (SGN-LIV1a) (NCT03310957), vic-trastuzumab duocarmazine (SYD985) (NCT04602117), anti-B7-H3-ADC (MGC018) (NCT03729596), CAB-ROR-ADC (BA3021) (NCT03504488), datopotamab deruxtecan (DS-1062) (NCT05374512) and tusamitamab Ravtansine (SAR408701) (NCT04659603) [ 22 ] ( Table 2 ).…”
Section: Emerging Drugs and Novel Combinations For Tnbcmentioning
confidence: 99%
“…However, more than 60 ADCs are at different stages of development for use in breast cancer patients, including several trials for TNBC, with molecular targets such as TROP-2, LIV-1, HER2, HER3 and ROR2, amongst others. The selected agents included in this review are trastuzumab deruxtecan (T-DXd) (NCT04556773), ladiratuzumab vedotin (SGN-LIV1a) (NCT03310957), vic-trastuzumab duocarmazine (SYD985) (NCT04602117), anti-B7-H3-ADC (MGC018) (NCT03729596), CAB-ROR-ADC (BA3021) (NCT03504488), datopotamab deruxtecan (DS-1062) (NCT05374512) and tusamitamab Ravtansine (SAR408701) (NCT04659603) [22] (Table 2). Abbreviations: Progression-free survival (PFS), overall survival (OS), response rate (RR), percentage of participants with adverse events (AEs), serious adverse events (SAEs), overall response rate (ORR), duration of response (DOR), clinical benefit rate (CBR), disease control rate (DCR), maximum tolerated dose (MTD), recommended phase II dose (RP2D), best overall response (OR), event-free survival (EFS), time-to-treatment failure (TTF), time to objective response (TTOR) and time to response (TTR).…”
Section: Exploring Combinations With Antibody-drug Conjugates (Adcs)mentioning
confidence: 99%